An N-linked disalicylaldehyde together with its caesium ion and dichloromethane sensing performances: 'dual key & lock' LMCT-enhanced fluorescence strategy. Issue 17 (10th July 2020) - Zhang, Kun; Chen, Ting-Ting; Shen, Yin-Jing; Yang, Zhuo-Ran; Huang, Yan; Zhang, Shishen; Xue, Jiadan; Li, Benxia
Abstract : The disalicylaldehyde-Cs + sensing system, a novel approach for quick and reusable detection of Cs + together with convenient CH2 Cl2 monitoring. Abstract : The development of inexpensive, selective and rapid-response chemosensors for detecting Cs + in waste water is highly desirable in the nuclear power industry. Here we demonstrate an efficient Cs + optical sensor based on the N-linked disalicylaldehyde H2 Qj with excited state intramolecular proton transfer (ESIPT), and it will transform into the ligand-to-metal charge transfer (LMCT) process in the presence of Cs +, resulting in dramatically enhanced fluorescence together with a distinct change of color from light-green to green-yellow. Simultaneously, it is found that CH2 Cl2 can serve as the quencher of LMCT-enhanced fluorescence, thus enabling selective CH2 Cl2 detection in a turn-off fluorescence approach. Further detailed studies reveal that both Cs + and CH2 Cl2 sensing processes are rapid within 60 seconds. The corresponding limit of detection (LOD) values for sensing Cs + and CH2 Cl2 are as low as 0.37 mM and 0.37%. Moreover, it was also verified that Cs + sensing is applicable in the range of pH = 7–11 and the reversibility of sensor H2 Qj can be easily achieved by modulating pH values, and H2 Qj is also assessed for its Cs + sensing performces in real water samples. This H2 Qj -Cs sensing system must provide a valuable reference for further Cs + sensors.